Reinterpretasi Tradisi Salim sebagai Sarana Internalisasi Nilai Karakter pada Anak Usia Dini - Shafa Alistiana Irbathy; Febriyani; Yuliana Nurshanti (Institut Agama Islam Negeri Madura, 2025)
Today's progressive modernization has brought a lot of change in the lives of people. However, the change that happens tends to end in a moral crisis. Especially educational institutions must be expected to be able to educate people with a soul, morality and good character. One of them through character formation that can be done by parents and teachers with this research, will be studied further in relation to the interaction of